VISUAL COMMUNICATION DESIGN OF SIGNAGE IN THE GENTALA ARASY JAMBI TOURIST AREA - Faradhiga, Aryadwipa Angesti; Y., Eva (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2025)
Gentala Arasy Tower is an icon of Jambi City and a tourist destination that residents and domestic tourists widely visit. The government targets Jambi as one of the provinces that makes the tourism sector one of the priorities for regional development. However, the infrastructure in the tourist area is not yet adequate to encourage this achievement, one of which is the absence of signage or a sign system and directions in the Gentala Arasy area. Signage is one of the important facilities to support the mobility of tourists or even residents who have never visited and do not know what is in the Gentala Arasy tourist area. The design of signage in the Gentala Arasy tourist area is expected to help tourists easily access tourist locations and public facilities properly and communicate important information while in the tourist area. The signage design is not only intended as a sign system and directions but also as a strengthening of the image and visual identity of the Gentala Arasy tourist area. The signage design uses bright colours with sans-serif typography so that visitors can easily recognise and read the signage, along with the information content and signs. The placement of signage in the tourist area is adjusted based on the category of form and function.